Incidence of Eye Affections in Dogs - Pandey, Priyanka; Shahi, A.; Kumar, D.; Shukla , M.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
A total of 8760 cases of dogs registered at TVCC of college of veterinary science and A.H. Jabalpur during the period of 9 months (August, 2015 to April, 2016) were screened. Out of these 3872 (44.20%) cases were referred to Department of Veterinary Surgery and Radiology, of which 122 (1.39%) dogs were suffering with various eye affections. Majority of the animals were affected with cataract (38.52%), followed by corneal ulcer (13.11%). The incidence of rest of the eye affections was less. Majority of animals were non-descript (38.62%), between 6 to 10 years (47.54%) of age. Sex wise incidence was higher in male (70.49%) dogs.